2012
DOI: 10.1111/j.1432-2277.2012.01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered balance between effector T cells and FOXP3+HELIOS+regulatory T cells after thymoglobulin induction in kidney transplant recipients

Abstract: Summary This study examined the effect of thymoglobulin induction therapy on leukocyte population dynamics in kidney transplant patients. Patients receiving standard immunosuppression were compared with those who received additional thymoglobulin at the time of kidney transplantation. Thymoglobulin induction led to an immediate and significant decrease of all T cells and NK cells, but not B cells or monocytes. CD8+ T cells recovered to near pretransplant level by 4 weeks post‐transplant. CD4+ T cells remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
3
23
0
10
Order By: Relevance
“…This is in line with earlier studies showing that anti-CD3 mAbs may induce Helios expression in Tregs, and that the Helios + Tregs produce less IFN-γ and IL2 [27]. Interestingly, it has been shown in kidney transplant recipients receiving ATG at the time of transplantation that depletion of CD4 + Helios + Foxp3 + T cells was less pronounced compared to CD4 + Foxp3 - T cells [28]. In kidney transplant patients, Bouvy et al found [29] an increase of the percentages of Tregs 6 months following ATG treatment in comparison with Basiliximab (anti-CD25 antibody) therapy.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with earlier studies showing that anti-CD3 mAbs may induce Helios expression in Tregs, and that the Helios + Tregs produce less IFN-γ and IL2 [27]. Interestingly, it has been shown in kidney transplant recipients receiving ATG at the time of transplantation that depletion of CD4 + Helios + Foxp3 + T cells was less pronounced compared to CD4 + Foxp3 - T cells [28]. In kidney transplant patients, Bouvy et al found [29] an increase of the percentages of Tregs 6 months following ATG treatment in comparison with Basiliximab (anti-CD25 antibody) therapy.…”
Section: Discussionsupporting
confidence: 89%
“…ATG induction therapy in vivo reduces the absolute number of Treg, but less than that for Tconvs, favorably altering the Treg/Tconv ratio 29,32,33 . Furthermore, Treg recover faster during immune reconstitution following ATG treatment, contributing to the sustained elevation of Treg/Tconv ratio 34 .…”
Section: Impact Of Approved Immunosuppressive Drugs On Tregmentioning
confidence: 99%
“…Elkord et al observed that there was an increased frequency of Helios + Tregs in the peripheral blood of patients with renal cell carcinoma, particularly after IL2 treatment (27). Another study revealed that there was a selective preservation of the Helios + Tregs in kidney transplant recipients that received thymoglobulin induction and a reduction in control patients (28). Similarly, others have noted an expansion of Helios + Tregs in patients with active systemic lupus erythematosus (29).…”
Section: Phenotypic Markersmentioning
confidence: 99%